Cosmeceutical Potential of Extracts Derived from Fishery Industry Residues: Sardine Wastes and Codfish Frames - Martim Cardeira; Ana Bernardo; Inês C. Leonardo; Frédéric B. Gaspar; Marta Marques; Rodrigo Melgosa; Alexandre Paiva; Pedro Simões; Naiara Fernández; Ana Teresa Serra (Antioxidants, 2022)
The fishery industry generates large amounts of waste (20–75% (w/w) of the total caught fish weight). The recovery of bioactive compounds from residues and their incorporation in cosmetics represents a promising market opportunity and may contribute to a sustainable valorisation of the sector. In this work, protein-rich extracts obtained by high-pressure technologies (supercritical CO2 and subcritical water) from sardine (Sardina pilchardus) waste and codfish (Gadus morhua) frames were characterized regarding their cosmeceutical potential. Antioxidant, anti-inflammatory and antibacterial activities were evaluated through chemical (ORAC assay), enzymatic (inhibition of elastase and tyrosinase), antimicrobial susceptibility (Klebsiella pneumoniae, Staphylococcus aureus and Cutibacterium acnes) and cell-based (in keratinocytes-HaCaT) assays. Sardine extracts presented the highest antibacterial activity, and the extract obtained using higher extraction temperatures (250 °C) and without the defatting step demonstrated the lowest minimum inhibitory concentration (MIC) values (1.17; 4.6; 0.59 mg/mL for K. pneumoniae, S. aureus and C. acnes, respectively). Codfish samples extracted at lower temperatures (90 °C) were the most effective anti-inflammatory agents (a concentration of 0.75 mg/mL reduced IL-8 and IL-6 levels by 58% and 47%, respectively, relative to the positive control). Threonine, valine, leucine, arginine and total protein content in the extracts were highlighted to present a high correlation with the reported bioactivities (R2 ≥ 0.7). These results support the potential application of extracts obtained from fishery industry wastes in cosmeceutical products with bioactive activities.